Integrating Safety Leadership, Safety Culture, Safety Behavior: Insight from the Manufacturing Industry - Rita Ambarwati (Research Parks Publishing LLC, 2026)
In the manufacturing sector, occupational safety is crucial since workplace mishaps put operations and worker health at serious danger. The purpose of this study is to examine how safety leadership influences good safety behaviour in the workplace and develops a safety culture. In order to assess the relationship between safety leadership and safety climate and to pinpoint the variables influencing leadership efficacy in enhancing safety procedures, this study used a methodical literature review technique. The findings demonstrate that the development of a positive safety culture, raising employee awareness, and promoting risk reporting are all greatly aided by effective safety leadership. The relationship between safety leadership and safety outcomes is mediated by safety climate, which makes the workplace safer and more cooperative. The systematic integration of safety leadership, safety culture, and safety behaviour, particularly in the Indonesian manufacturing sector, is identified as a knowledge gap in the literature by this study. Organisations can lower workplace accidents and boost overall safety performance by developing a proactive safety culture and bolstering safety leadership.